2011
DOI: 10.1371/journal.pone.0022641
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IGF-1 Signalling Enhances the Apoptotic Effect of AS602868, an IKK2 Inhibitor, in Multiple Myeloma Cell Lines

Abstract: Multiple myeloma (MM) is a B cell neoplasm characterized by bone marrow infiltration with malignant plasma cells. IGF-1 signalling has been explored as a therapeutic target in this disease. We analyzed the effect of the IKK2 inhibitor AS602868, in combination with a monoclonal antibody targeting IGF-1 receptor (anti-IGF-1R) in human MM cell lines. We found that anti-IGF-1R potentiated the apoptotic effect of AS602868 in LP1 and RPMI8226 MM cell lines which express high levels of IGF-1R. Anti-IGF-1R enhanced th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…It is noteworthy that RPMI-8226 cells were more sensitive to ZD55-TRAIL-induced cell death than MM1.S and MM1.R cells. This result is consistent with a previous finding that RPMI-8226 cells express more IGF-1R than MM.1S and U266 cells, and that the cytotoxic effect of anti-IGF-1R is more effective on MM cells with a high level of IGF-1R (20). Our data also showed that ZD55-TRAIL-mediated apoptosis and cell growth inhibition were not reversed by IGF.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It is noteworthy that RPMI-8226 cells were more sensitive to ZD55-TRAIL-induced cell death than MM1.S and MM1.R cells. This result is consistent with a previous finding that RPMI-8226 cells express more IGF-1R than MM.1S and U266 cells, and that the cytotoxic effect of anti-IGF-1R is more effective on MM cells with a high level of IGF-1R (20). Our data also showed that ZD55-TRAIL-mediated apoptosis and cell growth inhibition were not reversed by IGF.…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies suggest that the inhibition of IGF-1R decreases cell proliferation. Furthermore, combinations of multiple drugs such as the IKK2 inhibitor AS602868 and bortezomib with agents intervening in the IGF-1R pathway were found to result in enhanced apoptosis and reversal of drug-resistance (19,20,38), suggesting that targeting the IGF-1/IGF-1R axis is a promising approach for the treatment of MM. Our results confirm the inhibitory effect of ZD55-TRAIL on the expression of IGF-1R in RPMI-8226 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…I-kB kinase (IKK) inhibitors promote multiple myeloma cell apoptosis, and inhibition of IGF1 signaling enhances this effect (39). Therefore, inhibiting IGF1 signaling could enhance the use of IKK inhibitors for multiple myeloma treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Since previous studies have shown that NF-kB activity can regulate the expression of lncRNAs, we then also examined the effect of pharmacologic inhibition of IKK-2 on the IL-1b-stimulated production of CILinc01 and CILinc02. To this end we used TPCA-1, a known IKK-2 inhibitor (20,32,33). In cellfree enzymatic assays, TPCA-1 displays 22-fold selectivity for IKK-2 over IKK-1 and a .550-fold selectivity over other kinases, including MAP kinases and JNK kinases (32), though a recent study showed that in non-small cell lung cancer cell lines TPCA-1 also inhibited STAT-3 phosphorylation (34).…”
mentioning
confidence: 99%